The Effect of Media Exposure on the Instagram Account @Ruangnderes on Interest in Muroja'ah Al-Qur'an Students at Tahfidzul Qur'an Al-Hasan Pondok Ponorogo - Hanifatul Azizah; Andhita Risko Faristiana (EDUPEDIA Publisher, 2023)
Social media is increasingly in demand by various circles of society. This can be seen from the number of social media users who are increasing day by day. One of the fastest growing social media is Instagram. Many Instagram users, students and students who memorize the Al-Quran, use Instagram accounts to get information about da'wah. is to find out whether or not there is influence of media exposure from the Instagram account @ruangnderes on the interest of muroja'ah Al-Qur'an students at the Tahfidzul Qur'an Islamic Boarding School (PPTQ) Al-Hasan Ponorogo. This research method uses quantitative research. Data collection technique with a questionnaire. The data analysis used is a simple linear regression test. The results of the data analysis show that: there is the influence of media exposure of the Instagram account @ruangnderes on interest in muroja'ah Al-Qur'an Al-Hasan Ponorogo tahfidzul Qur'an Islamic Boarding School (PPTQ), with an analysis of the level of influence of media exposure of the Instagram account @ruangnderes on Islamic boarding school students tahfidzul Qur'an (PPTQ) Al-Hasan has a presentation of 76% and the level of interest in muroja'ah Al-Qur'an in Islamic boarding school students tahfidzul Qur'an (PPTQ) Al-Hasan Ponorogo is at a percentage of 74%, and results = 7.882 and = that is 1.996. Then it can be concluded hitung> t_table. So the results of this study indicate that there is a significant influence between media exposure to the Instagram account @ruangnderes on muroja'ah interest of 46%. with an analysis of the level of influence of media exposure from the Instagram account @ruangnderes on Al-Hasan Tahfidzul Qur'an Islamic Boarding School students (PPTQ) Al-Hasan has a presentation of 76% and the level of interest in muroja'ah Al-Qur'an among students of Tahfidzul Qur'an Islamic Boarding School (PPTQ) ) Al-Hasan Ponorogo is at a percentage of 74%, and the results = 7.882 and = 1.996. Then it can be concluded concluded t_count> t_table . So the results of this study indicate that there is a significant influence between media exposure to the Instagram account @ruangnderes on muroja'ah interest of 46%. with an analysis of the level of influence of media exposure from the Instagram account @ruangnderes on Al-Hasan Tahfidzul Qur'an Islamic Boarding School students (PPTQ) Al-Hasan has a presentation of 76% and the level of interest in muroja'ah Al-Qur'an among students of Tahfidzul Qur'an Islamic Boarding School (PPTQ) ) Al-Hasan Ponorogo is at a percentage of 74%, and the results = 7.882 and = 1.996. Then it can be concluded concluded t_(count )> t_table. So the results of this study indicate that there is a significant influence between media exposure to the Instagram account @ruangnderes on muroja'ah interest of 46%.